THE EFFECT OF COMPENSATION AND SHIFT WORK SYSTEM ONJOB SATISFACTION AMONG EMPLOYEES OF THE REGIONAL DISASTER MANAGEMENT AGENCY (BPBD) OF NORTH LABUHAN BATU REGENCY - Dosmatahi Sagala; Nilawati Nasti; Nelson Pinem (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the effect of compensation and shift work systems on employee job satisfaction at the Regional Disaster Management Agency (BPBD) of North Labuhan Batu Regency. Fair compensation and an effective work system are important factors in increasing job satisfaction, especially for employees who work in emergency and stressful conditions. This study used a quantitative method with a survey approach, where data were collected through questionnaires distributed to BPBD employees. The data analysis technique used multiple linear regression to test the relationship between the independent variables (compensation and shift work systems) and the dependent variable (job satisfaction). The results showed that compensation did not have a significant effect on employee job satisfaction. Similarly, the shift work system had a significant effect, although in some aspects it could reduce the level of job satisfaction due to changes in work rhythm and personal life balance. These findings indicate that to improve BPBD employee job satisfaction, a more optimal compensation policy is needed, along with a shift work system that considers employee welfare aspects. This study is expected to serve as a reference for policy makers in improving the welfare and work effectiveness of BPBD employees. The implications of this research are expected to serve as considerations for BPBD management and leaders in designing better compensation policies and work systems to improve employee well-being and performance. Suggestions for further research are also provided to explore other factors that may influence job satisfaction in greater depth.